Mechanistic Insights into a Stibene Cleavage Oxygenase NOV1 from Quantum Mechanical/Molecular Mechanical Calculations. Issue 2 (20th February 2019) - Lu, Jiarui; Lai, Wenzhen
Abstract: NOV1, a stilbene cleavage oxygenase, catalyzes the cleavage of the central double bond of stilbenes to two phenolic aldehydes, using a 4‐His Fe(II) center and dioxygen. Herein, we use in‐protein quantum mechanical/molecular mechanical (QM/MM) calculations to elucidate the reaction mechanism of the central double bond cleavage of phytoalexin resveratrol by NOV1. Our results showed that the oxygen molecule prefers to bind to the iron center in a side‐on fashion, as suggested from the experiment. The quintet Fe−O2 complex with the side‐on superoxo antiferromagnetic coupled to the resveratrol radical is identified as the reactive oxygen species. The QM/MM results support the dioxygenase mechanism involving a dioxetane intermediate with a rate‐limiting barrier of 10.0 kcal mol −1 . The alternative pathway through an epoxide intermediate is ruled out due to a larger rate‐limiting barrier (26.8 kcal mol −1 ). These findings provide important insight into the catalytic mechanism of carotenoid cleavage oxygenases and also the dioxygen activation of non‐heme enzymes. Abstract : Dioxygenase or monooxygenase ? QM/MM calculations for the oxidative cleavage of resveratrol by NOV1 support the dioxygenase mechanism involving a dioxetane intermediate. The Fe II ‐superoxo/substrate radical complex is identified as the reactive oxygen species.